Mechanistic insights into the PAI-1 inhibitor PAItrap3: enhancing lipid metabolism in adipose tissue of diabetic db/db mice - Wang, Linxi; Zhang, Zhouyangyang; Lin, Menghua; Qi, Liqin; Liu, Libin; Chen, Zhuo; Tang, Shuzhi; Wang, Lijing (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to investigate the effects of PAItrap3, a novel PAI-1 inhibitor, on lipid metabolism, and autophagy pathways in diabetic mice.Methodsdb/db diabetic mice were administered PAItrap3 (5.7 mg/kg/day, IV) for 21 consecutive days, and its impact on metabolic, gene expression, and lipidomic profiles was assessed. Western blot analysis was performed to examine lipid metabolism-related proteins in white adipose tissue (FASN, HSL, CPT1A, ACADM) and autophagy markers (LC3B, P62, Parkin, PGC1α, PPARGC1B). Additionally, RNA-seq and targeted lipidomics were employed to analyze gene expression and lipid metabolic alterations.ResultsPAItrap3 significantly reduced blood glucose and glycated hemoglobin levels while improving insulin sensitivity. In lipid metabolism, FASN and HSL levels were upregulated, whereas CPT1A and ACADM levels were downregulated in the DMP group. Regarding the autophagy pathway, PPARGC1B, LC3B, and PGC1α expression levels were increased, while P62 and Parkin levels were decreased. Lipidomics analysis revealed that triglycerides (TG) and diacylglycerols (DG) were generally downregulated, with TG (18:2/18:2/18:2) (0.96 [0.8491, 1]), LPI (18:0) (0.96 [0.8491, 1]), and MLCL (14:3/20:4/22:6) (0.96 [0.8491, 1]) identified as key metabolites.ConclusionThis study finds that PAItrap3 modulates lipid metabolism, energy homeostasis, and autophagy pathways, thereby improving metabolic dysfunction in diabetic mice. These findings highlight its potential therapeutic value for treating diabetes-associated lipid metabolic disorders.